Development and Testing of a Disease-Specific Health Literacy Measure in Kidney Transplant Patients. (September 2014) - Kazley, Abby Swanson; Jordan, Jessica; Simpson, Kit N.; Chavin, Kenneth; Rodrigue, Jim; Baliga, Prabhakar
Context: Health literacy affects a patient's ability to navigate through the system of care for late-stage kidney disease, including evaluation, waiting, and recovering from kidney transplant. Objectives: To develop and provide a preliminary evaluation of a knowledge and decision-making capacity tool, which is a component of health literacy. Design: Cross-sectional design with purposive sampling. Setting: Vascular access, dialysis, and outpatient transplant clinics. Methods: A Decision-Making Capacity Assessment Tool (DMCAT) was developed and administered to 127 adults at different stages in the kidney care process. Results: The DMCAT tool is positively and significantly correlated to the other 2 previously validated instruments and accounts for more variance than the other 2 tools in the regression models. We found significant differences in patients' health literacy and decision-making capacity related to their stage of care. Decision-making capacity appeared to be an important component of health literacy and should be considered as health care providers tailor care to meet patients' needs.